2019
DOI: 10.3390/metabo9060111
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Overview of Metabolomic Profile Changes in Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD), a common and heterogeneous respiratory disease, is characterized by persistent and incompletely reversible airflow limitation. Metabolomics is applied to analyze the difference of metabolic profile based on the low-molecular-weight metabolites (<1 kDa). Emerging metabolomic analysis may provide insights into the pathogenesis and diagnosis of COPD. This review aims to summarize the alteration of metabolites in blood/serum/plasma, urine, exhaled breath condensate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 108 publications
(127 reference statements)
2
29
0
Order By: Relevance
“…Several co-morbidities, such as chronic obstructive pulmonary disease (COPD), diabetes mellitus (DM) and other malignancies, were identified to be more prevalent in lung cancer patients compared to the general population [ 176 , 177 , 178 ]. The metabolomic profile of patients in disease states, such as COPD [ 179 ] and DM [ 180 ], were identified to be different from that of a normal population. While we excluded studies involving patients with other malignancies or having a history of any malignancy, we could not ascertain if patients were free of co-morbidities at the time of sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…Several co-morbidities, such as chronic obstructive pulmonary disease (COPD), diabetes mellitus (DM) and other malignancies, were identified to be more prevalent in lung cancer patients compared to the general population [ 176 , 177 , 178 ]. The metabolomic profile of patients in disease states, such as COPD [ 179 ] and DM [ 180 ], were identified to be different from that of a normal population. While we excluded studies involving patients with other malignancies or having a history of any malignancy, we could not ascertain if patients were free of co-morbidities at the time of sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, CS-induced excessive oxidative stress disrupts cell junctions between adjacent epithelial cells and induces apoptosis and necroptosis (cell death) in lung parenchyma, resulting in structural changes and COPD phenotypes [43][44][45]. Recent metabolomic studies identified metabolomic dysregulation in patient's samples with COPD, suggesting metabolic reprogramming as a part of COPD pathogenesis [46]. Short-term (4 and 8 weeks) CS exposure to A/J mice induced upregulation of genes encoding glycolysis, tricarboxylic acid cycle, mitochondrial fatty acid oxidation pathway, and redox regulation [47].…”
Section: Metabolic Reprogramming and Emphysemamentioning
confidence: 99%
“…Epidemiological studies indicate that obesity increases the risk of severe complications and death from influenza virus infections. 21 Plasma metabolomics profile in chronic pulmonary diseases has been associated with COMMENTARY metabolic dysfunctions leading to local and systematic inflammation, with more divergence as the disease gets more severe like in chronic obstructive pulmonary disease 22 and chronic obstructive lung disease. 23 Evidence also suggests that obesity might impact more than just disease severity as it not only alters innate and adaptive immune response, characterised by a state of chronic and low-grade inflammation, 24 it can also prolong virus shedding and increase the risk of viral transmission making the individual potentially more contagious.…”
Section: Perspective: Mainstream Precision Medicinementioning
confidence: 99%